A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF MAN 1 PEKANBARU IN READING NEWS ITEM TEXTS - Janatul Aliyah; Fadly Azhar; M. Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research was aimed to find out the ability of the first year students of MAN 1 Pekanbaru in reading news item texts. The research data were collected from July to August 2016. The subject of this research was class X MIA 2. which consisted of 28 students. The data were collected by giving a test to the students in the form of multiple choice test. The results of the research showed that the first year students of Man 1 Pekanbaru got good level in terms of finding language features with mean score of 78.5, mediocre level in terms of finding generic structures with mean score of 58.5. Therefore, it can be concluded that the ability of the first year students in reading news item texts was in term of finding language features.Keywords: Students’ ability, News Item texts